Modelling the progression of neurodegenerative diseases - Laranjeira, S (2017)
Neurodegenerative disease is an umbrella term for pathologies that primarily damage neurons. As their incidence increases with age it is becoming of a greater concern for the west, due to its aging population. Due to their chronic nature and the difficulty to create reliable and reproducible animal models of these diseases their pathophysiologies are still poorly understood. For all these reasons, a mathematical modelling approach is suggested. The methodology of the work here consisted of identifying the state of the art models that describe the healthy behaviour of cells (e.g. metabolism and ionic regulation) and adapting them for pathological environments. With these models hypotheses provided by clinicians and pathologists were tested. The work focuses on developing models of mechanisms common to neurodegenerative diseases, which include: glutamate excitotoxicity, aquaporin water kinetics, inflammatory complement lysis and acute inflammation. Glutamate excitotoxicity was modelled by creating a compartmental model of glutamate exchange between neurons and astrocytes. This model was the first model of glutamate kinetics validated in an ischaemic stroke context. The aquaporin water kinetics and complement lysis models were developed in the context of the autoimmune disease Neuromyelitis Optica. Through this project a hypothesised trigger for the pathology was confirmed. Additionally, the first model of astrocytic cytotoxic oedema due to complement lysis was developed. Finally, a preventative drug for complement lysis was simulated. Acute inflammation was explored in the context of understanding the potential of chemerin as a pro-resolving cytokine. To that effect, a model of acute inflammation was developed where pro-resolving mechanisms were included. This model was the first to attempt model the effects of an intervention in inflammation. The results indicated that there is a maximum inhibitory effect of chemerin on inflammation. Additionally, two preventive avenues for chronic inflammation were found. With this work, the first attempts of capturing relevant mechanisms of neurodegenerative diseases were presented. These models can now be further developed and adapted to other pathological environments.